Nové pohl'ady na epidemiológiu tyreopatií - Langer, P (Vnitrni lekarstvi, 2006)
Due to successful progress in monitored iodine prophylaxis of iodine deficiency during the last decades the prevalence of endemic goitre in several countries considerably decreased. Nevertheless, epidemiological studies have been also indicating a certain prevalence of small thyroids in the areas of iodine deficiency too, and, vice versa, that even after successful iodine prophylaxis the thyroid volume (ThV) is not equally decreasing in all subjects and goitre does still exist. This phenomenom has been called sporadic goitre and hereditary etiological factors were suspected. It is shown that after 40 years of successfully monitored and mandatory consumption of iodized salt in Slovakia the distribution of ThV in 2661 adults has considerably decreased as compared to that of 1380 adults from Germany and Denmark where median iodine deficiency was still present around 1990. However, in spite of that, in those 2661 adults from Slovakia the average ThV in the upper quartile was 22.5 ml which was 4-times higher than the value in the lower quartile (6.3 ml) or about twice as much as that in the second (9.4 ml) or third quartile (12.7 ml). Such differences possibly cannot be explained by considerable differences in life-long iodine intake any more and that is the reason why some factors different from iodine deficiency should be taken into account. Among them perhaps hereditary factors (including ethnical and autoimmune ones) and environmental factors (such as persistent chlorinated pollutants) should be considered first. It is postulated that sufficient iodine intake in Slovakia for last 40-50 years is a prerequisite for evaluating the role of such factors. Short overview of epidemiological studies from Slovakia published elsewhere is presented showing possible participation of hereditary factors. Thus, one study showed increased thyroid growth in a group of children followed for 7 years which was independent of iodine supplementation. Another study showed significantly different ThV in several pairs of siblings born within the interval of less than 24 months. Since such siblings took the same meals for the whole life in the same family and in the same school, they apparently had about the same life-long intake of iodine and thus the differences in ThV cannot result from iodine deficiency of one member of the pair. In addition, possible effect of environmental pollutants on ThV in a cohort of more than 2 000 adults with the same long-term iodine intake was observed. Finally, it is underlined that the upper limit of optimal iodine intake starts to be equally important as the lower limit and that such circumstance turns out to be of considerable importance. Japan is presented as a country with historically permanent very high iodine intake where any problem of endemic goitre from iodine deficiency never existed. However, possibly reversible goitre from megadoses of iodine exists, while the question of prevalence of autoimmune thyroid disorders does not seem to be definitely solved because of the lack of large epidemiological surveys in general population.
Keywords: Female; lidé středního věku; Adolescent; mužské pohlaví; Humans; dospělí; Slovakia; lidé; Middle Aged; senioři; ženské pohlaví; Child; jod; Aged; struma; Iodine; dítě; Adult; Male; mladiství; Goiter; Slovenská republika